Enhancing Natural Resource Programs with Field Trips - Julie Athman; Martha C. Monroe (EDIS, 2009)
FOR-105, a 5-page illustrated fact sheet by Julie Athman and Martha C. Monroe, explains how to maximize learning during the field trip to ensure that students gain its cognitive and affective benefits. Includes references. Published by the UF School of Forest Resources and Conservation, July 2002. Reviewed October 2008.